Effect of modified indwelling needle insertion techniques in Chinese children: a systematic review and meta-analysis - Hou, Hongmei; Chen, Linhui; Liu, Liping; Yan, Xiangyu; Li, Huan; Pan, Xinyu; Jin, Mengyan (Frontiers in Pediatrics, 2025)
AimA comprehensive study evaluated the effect of modified indwelling needle technique on puncture success rate and indwelling time in Chinese children.BackgroundCompared with ordinary steel needles, indwelling needles have many advantages. The incidence of complications of an indwelling needle is lower than that of an ordinary steel needle. There are many ways to improve it, such as a modified fixation and liquid connection indwelling needle, and many studies have conducted randomized controlled trials.Designmeta-analysisMethodsDatabases including PubMed, Web of Science, CNKI, Wang Fang, CQVIP, Embase were electronically searched for studies on modified indwelling needle insertion techniques from inception to June 20, 2024. Two authors conducted the article search independently. A third author addressed the inconsistencies that arose between the two authors. Keywords were used for retrieval, and Boolean operators were used accordingly.ResultsA total of 18 randomized controlled (RCT) studies were included. The results showed that the puncture success rate, indwelling time and parent satisfaction of the modified indwelling needle insertion technique were better than the control group. Sensitivity analysis was carried out after each study was excluded one by one, and the results showed that pooled sensitivity and specificity had no significant change, indicating that the stability of the meta-analysis, and no publication bias found.ConclusionsThe modified indwelling needle technique showed increased puncture success rate, prolonged indwelling time and improved parental satisfaction compared with the control group.